2008
DOI: 10.1143/jpsj.77.054711
|View full text |Cite
|
Sign up to set email alerts
|

Holes in the Valence Band of Superconducting Boron-Doped Diamond Film Studied by Soft X-ray Absorption and Emission Spectroscopy

Abstract: Carbon-and boron-2p states of superconducting and non-superconducting boron-doped diamond samples are measured using soft X-ray emission and absorption spectroscopy. For the superconducting sample, a large density of hole states is observed in the valence band in addition to the states in the impurity band. The hole states in the valence band is located at about 1.3 eV below the valence band maximum regardless of the doping level, which cannot be interpreted within a simple rigid band model. Present experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Due to core shift to smaller binding energy at the C1 site, hole-doping states at the C1 site is shifted from those at the others. This calculated feature is in good agreement with the ''H'' and ''I'' structures in the experimental XAS spectra by Nakamura [15]. As the B concentration increases (from C 63 B to C 31 B), XAS spectrum at the hole states is amplified while the energy difference between the two structures is unchanged.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Due to core shift to smaller binding energy at the C1 site, hole-doping states at the C1 site is shifted from those at the others. This calculated feature is in good agreement with the ''H'' and ''I'' structures in the experimental XAS spectra by Nakamura [15]. As the B concentration increases (from C 63 B to C 31 B), XAS spectrum at the hole states is amplified while the energy difference between the two structures is unchanged.…”
Section: Resultssupporting
confidence: 87%
“…It has been found that the heavily doped sample shows asymmetric peak and lower-binding feature simultaneously. Nakamura et al have measured X-ray emission spectroscopy (XES) and X-ray absorption spectroscopy (XAS) at B and C K-edges [14,15]. B K-edge XES shows hole-doping feature similar to Yokoya's SXARPES.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the impurity concentration n imp in our definition corresponds to the concentration of isolated substitutional boron acceptors. It has been pointed out that the concentration of carries is different from that of boron atoms owing to the presence of B-H complex and/or B-B dimer and the superconducting T c is determined by the concentration of carriers [43,65]. We have confirmed that the B-H complex or B-B dimer neither enhance nor suppress the superconductivity [66].…”
Section: Doping Dependencesupporting
confidence: 67%
“…Many experimental and theoretical studies have focused on the origin of the metallic nature responsible for superconductivity in diamond. Investigations continue to clarify whether it originates from the holes at the top of the diamond valence band or from the boron impurity band formed above the valence band [5][6][7][8][9][10][11][12][13][14][15]. In particular, a higher-T c superconductivity in C:B has been suggested from a theoretical model by a Japanese group [16][17][18], where bonds transform into bands by carrier doping of a semiconductor.…”
Section: Introductionmentioning
confidence: 99%